Handbook of veterinary neurology - Lorenz, Michael D. (Elsevier/​Saunders, 2011)
Handbook of Veterinary Neurology provides quick access to vital information on neurologic conditions in a wide range of species, including canine, feline, bovine, caprine, equine, ovine, and porcine. A problem-oriented approach makes it easy to diagnose and treat neurologic problems in small and large animals. The coverage of disorders by problem, not by established disease diagnosis, emulates how animals present to the veterinary hospital and simplifies the formulation of a correct diagnosis. Within each chapter, discussions of neurologic disease include a review of the localization criteria and the diseases that can cause that problem, plus treatment and surgical techniques. Lead author Michael D. Lorenz brings decades of experience to neurologic assessment, using a diagnostic approach that requires minimal knowledge of neuroanatomy.